SOME PHILOSOPHICAL PROBLEMS OF MANAGEMENT OF COLLECTIVES - Zoya V. Bezveselnaya (Вестник Российского экономического университета имени Г. В. Плеханова)
Realities of modern Russian society, growth of consciousness of the people set new tasks for management. Article is devoted to problems of development of humanistic management in Russia. The author has concentrated attention on the philosophical questions arising in management in the course of formation of corporate culture of work collectives. The main requirements to humanistic management, and also his main principles are defined, the analysis of opportunities of philosophy of management and other social sciences in creation of the Russian model of effective management is given. The author finds out specifics of national mentality of Russians in relation to economic activity and problems of subjects of management in this sphere of public life.